Automated Quality Assurance of OAR Contouring for Lung Cancer Based on Segmentation With Deep Active Learning - Men, Kuo; Geng, Huaizhi; Biswas, Tithi; Liao, Zhongxing; Xiao, Ying (Frontiers in Oncology, 2020)
Purpose: Ensuring high quality data for clinical trials in radiotherapy requires generation of contours that comply with protocol definitions. The current workflow includes manual review of the submitted contours, which is time-consuming and subjective. In this study, we developed an automated quality assurance (QA) system for lung cancer based on a segmentation model trained with deep active learning. Methods: Data included a gold atlas with 36 cases and 110 cases from the “NRG Oncology/RTOG 1308 trial”. The first 70 cases enrolled to the RTOG 1308 formed the candidate set, and the remaining 40 cases were randomly assigned to validation and test sets (each with 20 cases). The organs-at-risk included the heart, esophagus, spinal cord, and lungs. A preliminary convolutional neural networks segmentation model was trained with the gold standard atlas. To address the deficiency of the limited training data, we selected quality images from the candidate set to be added to the training set for fine-tuning of the model with deep active learning. The trained robust segmentation models were used for QA purpose. The segmentation evaluation metrics derived from the validation set, including the Dice and Hausdorff distance, were used to develop criteria for QA decision making. The performance of the strategy was assessed using the test set. Results: The QA method achieved promising contouring error detection, with the following metrics for the heart, esophagus, spinal cord, left lung, and right lung: balanced accuracy, 0.96, 0.95, 0.96, 0.97, and 0.97, respectively; sensitivity, 0.95, 0.98, 0.96, 1.0, and 1.0, respectively; specificity, 0.98, 0.92, 0.97, 0.94, and 0.94, respectively; and area under the receiving operator characteristic curve, 0.96, 0.95, 0.96, 0.97, and 0.94, respectively. Conclusions: The proposed system automatically detected contour errors for QA. It could provide consistent and objective evaluations with much reduced investigator intervention in multicenter clinical trials.